If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 9 = -1(2x + 2) Reorder the terms: 9 + X = -1(2x + 2) Reorder the terms: 9 + X = -1(2 + 2x) 9 + X = (2 * -1 + 2x * -1) 9 + X = (-2 + -2x) Solving 9 + X = -2 + -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + X = -2 + -9 + -2x Combine like terms: 9 + -9 = 0 0 + X = -2 + -9 + -2x X = -2 + -9 + -2x Combine like terms: -2 + -9 = -11 X = -11 + -2x Simplifying X = -11 + -2x
| 33-6x=-24 | | 2x^3-72x= | | 3+4(3n+6)-n= | | p^2-6p+5=0 | | [9(b+4)-15]-[3(b-4)+3]= | | bc=3x+2 | | .05x+13=9 | | 5r-2r+3=7r-r | | 7x^2-7x-84= | | -2y=10x+16 | | (3x+5)(x+3)=7 | | 6x-y+5=180 | | 7x-248+x+44=180 | | 30-4x=14 | | 5(x-7)=2(2-2x)-3 | | [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) | | 2x+55=272 | | (4y-7)+(-2y+5)= | | 2/5(x+3)=6 | | 3x+7-8(x+2)=-36 | | N(N-3)=700 | | 23-4x=9 | | 16x^4-54x= | | 9w-28=2 | | 4a-4=4x+4-2x | | 4t^2-16t+7=0 |